Participação do sistema endocanabinoide em modelos animais de efeitos adversos motores induzidos pelo haloperidol - Jivago Röpke Rodrigues (2017)
Schizophrenia is a psychiatric disorder in which symptoms are disconnection with reality, mood and cognition alterations. The main treatment consists in antipsychotic drugs, which mainly act as dopamine D2 receptor antagonists. Through this mechanism, some antipsychotics induce serious motor side effects, such as parkinsonian syndrome at the beginning of treatment and tardive dyskinesia after chronic treatment. Physiologically, dopaminergic neurons may be under control of the endocannabinoid system, consisting of the endocannabinoids anandamide and 2-aracnodoylglycerol (2-AG), their enzymes of synthesis and hydrolysis, as well as for their receptors. Considering these evidences, the present study aimed to test the hypothesis that the administration of endocannabinoid hydrolysis inhibitors attenuates the motor alterations induced by haloperidol. . Were used predictive animal models of acute motor side effects, catalepsy, in mice, and chronic, vacuous chewing movements (VCM), in rats. In addition, the participation of CB1, TRPV1 and 5-HT1A receptors was verified in these effects. The results showed that the increase in endocannabinoid levels, by inhibiting the enzymes responsible for their degradation, attenuates the acute and chronic motor adverse effects induced by haloperidol. Inhibition of anandamide hydrolysis attenuates catalepsy via activation of TRPV1 receptors and tardive dyskinesia via activation of CB1 receptors. Inhibition of 2-AG hydrolysis inhibits catalepsy and tardive dyskinesia through the activation of CB1 receptors. 5-HT1A receptors do not appear to be involved. In addition, in animals chronically treated with haloperidol, there was an increase in CB1 receptor expression, exclusively in those in which the drug actually induced increase of VCMs. These results are consistent with the hypothesis that the endocannabinoid system modulates the adverse motor effects induced by haloperidol.